2012
DOI: 10.1016/j.jamcollsurg.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A Progressive Postresection Walking Program Significantly Improves Fatigue and Health-Related Quality of Life in Pancreas and Periampullary Cancer Patients

Abstract: A progressive postresection walking program significantly improves fatigue and health-related quality of life in pancreas and periampullary cancer patients. Recommended Citation Yeo, Theresa; Burrell, Sherry A; Sauter, Patricia K; Kennedy, Eugene P; Lavu, Harish; Leiby, Benjamin E; and Yeo, Charles, "A progressive postresection walking program significantly improves fatigue and health-related quality of life in pancreas and periampullary cancer patients." (2012 Methods:One hundred and two patients with resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(184 citation statements)
references
References 39 publications
4
177
0
3
Order By: Relevance
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…A 2012 RCT of a home walking programme in 102 postoperative pancreas and periampullary cancer patients also demonstrated reduction in fatigue levels, as well as improvement in anxiety and depression, in the walking group as compared to the usual care group. 1 Although resistance training and mind-body techniques did not achieve significance, this may have been owing to small sample size or insensitive outcome measures and are not indicative of the individual benefits realised with those programmes. These modalities remain to be prospectively evaluated in large-scale longitudinal investigations.…”
Section: Commentarymentioning
confidence: 95%
“…Seventeen rcts [22][23][24]27,29,[30][31][32][33]37,39,42,45,47,[51][52][53] found that no adverse events or side effects were attributable to the exercise program. Seven 26,28,34,35,40,46,50 did not report on adverse events at all. Three rcts 25,41,44 reported adverse events that were deemed not to be related to the intervention; two 36,38 reported events that were attributable to the intervention (3 patients experienced muscle soreness, and 2 experienced musculoskeletal injury).…”
Section: Commentsmentioning
confidence: 97%
“…Fourteen systematic reviews [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] found an improvement in qol for people with cancer participating in an exercise intervention during the active treatment or post-treatment periods (Table v). Of the sixteen rcts involving patients in active treatment [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , seven reported significant differences between the intervention and control groups (Table vi) 23,24,26,[31][32][33]36 . In the thirteen posttreatment intervention studies [38][39][40][41][42][43][44]…”
Section: Qol and Muscular And Aerobic Fitnessmentioning
confidence: 99%
See 1 more Smart Citation